Molecular Mechanisms of Methylglyoxal in Diabetes-related Macrovascular Complications - Meiliana, Anna; Dewi, Nurrani Mustika; Wijaya, Andi (The Indonesian Biomedical Journal, 2024)
Diabetes mellitus (DM) is a chronic endocrine and metabolic disease indicated by the presence of hyperglycemia. It has been known that hyperglycemia and oxidative stress are the main culprit of all DM complications, including macrovascular complications. As a byproduct of lipid, protein, and carbohydrate metabolism, methylglyoxal (MGO) is a highly reactive substance which plays a positive signaling role in helping cells regain redox balance under oxidative stress circumstances. DM-related problems lead to an excess of mitochondrial superoxide in the heart and big and small vascular endothelial cells. Elevated intracellular reactive oxygen species induce impaired angiogenesis in reaction to ischemia, trigger several proinflammatory pathways, and result in enduring epigenetic modifications that propel the continuous expression of proinflammatory genes even after glucose levels return to normal. Over time, the significance of the extremely quick advanced glycation end-products (AGE) production caused by the extremely reactive MGO has been clarified. It is now evident that MGO causes vascular tissue to react maladaptively. Glyoxalase 1 (GLO1) is the primary enzyme in an organism's enzymatic glyoxalase defense mechanism, which converts MGO to D-lactate in order to counteract the harmful effects of MGO. Understanding the role of the MGO–GLO1 pathway in the etiology of vascular disease in diabetes has advanced significantly. Therefore, it can be summarized that vascular damage are linked to diabetes. The AGE precursor MGO are important in determining the connection between diabetes and vascular damage. MGO and AGEs play a role in several phases of the development of diabetes complications. MGO and AGEs may be useful therapeutic targets for diabetes's macrovascular problems.KEYWORDS: hyperglycemia, AGE, methylglyoxal, glyoxalase, D-lactate, gluthatione, oxidative stress